Quality Assurance in Higher Education Institutions: The Case of Tribhuvan University - Pun, Min (SCHOLARS: Journal of Arts & Humanities, 2020)
The main objective of this paper is to illustrate the current status of quality assurance practices and identify challenges and opportunities facing Tribhuvan University (TU) in general and higher education institutions of TU in particular. Apart from a range of benefits and prospects from adopting and implementing the Quality Assurance and Accreditation (QAA) system within TU, it has been facing a number of challenges in maintaining quality in its higher education institutions. In return, the implementation of the system can create a number of opportunities, particularly it has to internationalize its higher education and show a strong presence in the world university rankings. In order to meet this objective, the study has used a descriptive-analytical approach to find out the issues related to quality assurance in higher education institutions. Finally, the paper has made important policy implications and recommendations to support the ongoing efforts of UGC, Nepal and maintain and ensure quality in higher education institutions of TU.